2020
DOI: 10.1515/hc-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel biological tetracoumarin derivatives bearing ether moieties

Abstract: A series of novel tetracoumarin derivatives (3a-f) were prepared using the reaction of ether functionalized dibenzaldehyde with 4-hydroxycoumarin in the presence of sodium acetate. The structure of compounds was validated by IR, NMR, and CHN analyzes. Antimicrobial (antibacterial and antifungal) activity was studied on the basis of the minimum bactericidal concentration, minimum inhibitory concentration and inhibitory zone diameter. Favorable biological activity was found in compound 3f.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The intermediate (3) was obtained as a yellow compound in high yield. The structure of (3) was confirmed based on its HRMS, IR, 1 H-NMR and 13 C-NMR spectra.…”
Section: A D V N C E D O N L I N E a R T I C L Ementioning
confidence: 97%
See 2 more Smart Citations
“…The intermediate (3) was obtained as a yellow compound in high yield. The structure of (3) was confirmed based on its HRMS, IR, 1 H-NMR and 13 C-NMR spectra.…”
Section: A D V N C E D O N L I N E a R T I C L Ementioning
confidence: 97%
“…Subsequently, the coumarin-quinone hybrids (5) were obtained from (3) and the corresponding salicylaldehyde (4) in the presence of a few drops of piperidine, followed by neutralization with diluted HCl. Four coumarin-quinone hybrids abbreviated as DTBSA, DTBSC, DTBSB and DTBSN were obtained and purified, followed by characterization using HRMS, FTIR, 1 H-NMR and 13 C-NMR spectroscopy.…”
Section: A D V N C E D O N L I N E a R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…In another route, the researchers' interests were focused on the synthesis of enaminonitriles of this type of bicyclic pyranopyrimidines owing to the high stability of the nitrile group relative to the ester group. Consequently, Behzadi et al 41 reported the synthesis of pyranopyrimidine 2a–j ( Scheme 1 ) bicyclic systems with an enaminonitrile moiety at the pyran ring by a green protocol involving the utility of mefenamic acid as a catalyst. Therefore, reactions of aryl aldehydes with malononitrile, and barbituric acid in ethanol at reflux temperature gave the desired pyranopyrimidines with improved yields (90–98%).…”
Section: Synthesis Of Bicyclic Systemsmentioning
confidence: 99%